2019
DOI: 10.1016/j.cell.2019.01.006
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal-Transport Analysis of Single-Cell Gene Expression Identifies Developmental Trajectories in Reprogramming

Abstract: Highlights d Optimal transport analysis recovers trajectories from 315,000 scRNA-seq profiles d Induced pluripotent stem cell reprogramming produces diverse developmental programs d Regulatory analysis identifies a series of TFs predictive of specific cell fates d Transcription factor Obox6 and cytokine GDF9 increase reprogramming efficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
617
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(691 citation statements)
references
References 72 publications
(79 reference statements)
15
617
2
Order By: Relevance
“…S2A). This contrasted with previous studies that reported reactivation of X-linked genes only much later in reprogramming, after activation of late pluripotency markers and complete Xist silencing (Pasque et al 2014;Schiebinger et al 2019). Other genes were delayed in transcriptional reactivation and could be segregated into different groups: with reactivation kinetics between day 8 and day 10 ("intermediate"), between day 10 and day 13 ("late"), and after day 13 ("very late") ( Fig.…”
Section: Transcriptional Reactivation Of X-linked Genes During Inductcontrasting
confidence: 98%
See 2 more Smart Citations
“…S2A). This contrasted with previous studies that reported reactivation of X-linked genes only much later in reprogramming, after activation of late pluripotency markers and complete Xist silencing (Pasque et al 2014;Schiebinger et al 2019). Other genes were delayed in transcriptional reactivation and could be segregated into different groups: with reactivation kinetics between day 8 and day 10 ("intermediate"), between day 10 and day 13 ("late"), and after day 13 ("very late") ( Fig.…”
Section: Transcriptional Reactivation Of X-linked Genes During Inductcontrasting
confidence: 98%
“…1G). An analysis of single-cell RNA-seq iPSC reprogramming data in a different reprogramming system and genetic background (Schiebinger et al 2019) confirmed the finding that different groups of X-linked genes are activated at different times during pluripotency induction ( Fig. 2C,D; Supplemental Fig.…”
Section: Transcriptional Reactivation Of X-linked Genes During Inductsupporting
confidence: 67%
See 1 more Smart Citation
“…S17B). Optimal transport is a technique for measuring distances between equally sized samples that has been applied to a wide variety of data analysis tasks, including scRNA-seq (Schiebinger et al 2019).…”
Section: Endothelial Cells and Lymphocytes Show Distinct Aging Trajecmentioning
confidence: 99%
“…These methods may be used to map and interpret novel cell states 463 predicted by mathematical models or similarly as a method to interpret model-predicted 464 changes in cell heterogeneity following a perturbation. 465 Schiebinger et al compute and predict differentiation trajectories in cell development 466 using optimal transport (OT) [35]. This approach considers the optimal transport of 467 cells as a mass flowing along differentiation trajectories, and is conceptually the most 468 similar to our approach.…”
mentioning
confidence: 99%